ANALYSIS OF THE ANABOLIC WINDOW BEHAVIOUR IN PHYSICALLY ACTIVE INDIVIDUALS: A LITERATURE REVIEW - Huarte Prieto, Josu; Yanci Irigoyen, Javier (MHSalud: Revista en Ciencias del Movimiento Humano y Salud, 2016)
The purpose of this review was first to determine whether there is enough evidence in scientific literature to insure the existence of the anabolic window subsequent to training sessions to improve muscle adaptations of hypertrophy and strength by ingesting certain nutrients during a period of time. The review was also aimed at establishing if there is a limited time of action for such an anabolic window and finally at analyzing which are the appropriate nutritional recommendations for the training sessions given in the various scientific papers. Information was searched using the PubMed search engine (in English) and Google scholar and Dialnet (in Spanish). The search was narrowed to only articles directly related to training and articles with healthy subjects with no pathologies. Given that the studies analyzed present mixed and contradictory results, it is difficult to determine the existence or non-existence of the anabolic window and its time of action.